The Oklahoma City National Memorial: collective narratives in memorial design - Mahaney, Nancy (My University, 2026)
This study adds to the understanding of the social role of designed memorials constructed at the sites of trauma by examining the memorial development process, the stated intent of the memorial design, and the public experience of the memorial space. The research site selected for this study is the Oklahoma City National Memorial (OKCNM), constructed on the site of the Alfred P. Murrah Federal building in downtown Oklahoma City. A domestic terrorist attack against federal agencies and their employees took place in 1995; the bombing killed 168 people and left many others physically and emotionally injured, orphaned and homeless. This event is recognized as the most destructive domestic terrorist attack in the United States’ history. As the physical manifestation of a collective design process, the memorial symbolizes the community’s experience of the event and shares that experience with visitors through a carefully constructed set of narratives. The symbolic memorial along with texts and rhetorical materials created and disseminated by the OKCNM together form the site’s intended narratives. These narratives are communicated experientially, visually, and didactically using signs and symbols, interpretive texts, staged events, public speeches, and publications. This study documents these narratives through archival research that explores the process by which these intended narratives were conceived, developed, and disseminated during the initial creation and subsequent interpretation of the symbolic memorial. On-site observations document the ways visitors are using the memorial spaces, while surveys of memorial visitors document their reported experiences of the symbolic memorial. A comparison of the intended narratives revealed through document analysis with visitors’ responses to surveys reveals the extent to which the memorial design is meeting the goals and objectives defined for the visitor’s experience of the memorial design.
Keywords: Oklahoma City National Memorial, Collective memory, Environmental design, Narrative analysis, Visitor use studies, Urban planning